The effects of LPM570065, a novel triple reuptake inhibitor, on extracellular serotonin, dopamine and norepinephrine levels in rats. - Renyu Zhang; Xiang Li; Yanan Shi; Yufeng Shao; Kaoxiang Sun; Aiping Wang; Fengying Sun; Wanhui Liu; Di Wang; Jingji Jin; Youxin Li (PLoS ONE, 2014)
Triple reuptake inhibitors (TRIs) are currently being developed as a new class of promising antidepressants that block serotonin (5-HT), dopamine (DA) and norepinephrine (NE) transporters, thereby increasing extracellular monoamine concentrations. The purpose of this study was to investigate the effects of LPM570065, a novel TRI and a desvenlafaxine prodrug, on extracellular 5-HT, DA and NE levels in the rat striatum after acute and chronic administration relative to desvenlafaxine, using High Performance Liquid Chromatography (HPLC) and microdialysis. Acute administration was performed by providing rodents with oral solutions (0.06 mmol·kg(-1) p.o.), oral suspensions (0.06 mmol·kg(-1) p.o.) and intravenous solutions (0.04 mmol·kg(-1) i.v.) of LPM570065 and desvenlafaxine. Oral suspensions (0.06 mmol·kg(-1)·day(-1)) of the two drugs were also administered for a 14-day chronic period. HPLC analysis revealed that LPM570065 rapidly penetrated the rat striatum, converted into desvenlafaxine and exhibited larger total exposure compared with the administration of desvenlafaxine. Microdialysis revealed that acute and chronic administration of oral suspension of LPM570065 increased the 5-HT, DA and NE levels more than the relative administration of desvenlafaxine. Unlike desvenlafaxine, acute administration of an intravenous LPM570065 solution did not induce the undesirable 90% decrease in extracellular 5-HT levels. In contrast to the fully dose-dependent elevation of 5-HT induced by desvenlafaxine, the acute administration of LPM570065 showed a capped increase in extracellular 5-HT levels when combined with WAY-100635. Additionally, forced swim test demonstrated that acute and chronic administration of LPM570065 reduced the immobility time more than the relative administration of desvenlafaxine. These data suggest that LPM570065 may have greater efficacy and/or a more rapid onset of antidepressant action than desvenlafaxine and also counterbalance the harmful effects of desvenlafaxine on 5-HT neurotransmission related to 5-HT1A autoreceptors. Thus, this new class of drugs, TRIs has the potential to provide a new therapeutic mechanism for treating depression.